Psychometric properties of the Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ-12) on Chilean women (Colombia Medica, 2021)
Introduction:Pelvic floor dysfunctions have an impact on women’s sexual function. A Chilean study found that 74% of women have pelvic floor dysfunctions, but there is no validated tool for them.Objective:To evaluate the psychometric properties of the Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ-12) for assessing sexual function in Chilean women with pelvic floor dysfunctions.Methods:A cross-sectional study of psychometrics in 217 women with pelvic floor dysfunction, age 18 or older, and sexually active (last 6 months). Non-probability, convenience sampling. Tool: PISQ-12. Experts checked content validity, construct validity with confirmatory factor analysis, reliability with Cronbach’s alpha, and discriminating capacity with Pearson and McDonald’s omega.Results:The population is mainly perimenopausal, highly educated with no income and with urinary incontinence (89.4%). The psychometric analysis supports a three-factor structure: sexual response, female sexual problems, and male sexual problems, with a good (α= 0.85), acceptable (α= 0.73), and poor (α= 0.63) reliability, respectively, but McDonald’s omega was acceptable for all three. These were related to age (rs: -0.33), education (rs: 0.36), number of pregnancies (rs: -0.18) and vaginal births (rs: -0.25).Conclusions:PISQ-12 is valid and reliable for measuring sexual dimensions and problems. Age, education, and a number of pregnancies and vaginal births are moderately correlated to sexual response.